The influence of overload training on cyclists T-Lymphocyte subsets, NK% and the effectiveness of controlling changes by electric-acupuncture before competition - Ma, H.; Wu, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Distance cycling is a sport where the athletes` aerobic capacity is one of the main elements that determine performance in competition. To build endurance capacity, athletes involved in this sport should undertake highly intense overload training for several months before competition. After this training, whilst the competitive ability of athletes may be at a prime, the competency of their immune system is frequently compromised which leaves them at a high risk for infection. Acupuncture is a facet of Chinese medicine which acts to "re-program" and restore normal functions by stimulating certain points on the meridians in order to release the Chi energy. The connections between the points ensure that there is a balance between Yin and Yang, which means energy is free to constantly flow up and down these pathways. When pathways become obstructed, deficient or excessive, Yin and Yang are said to be thrown out of balance which can leave a human prone to illness. Acupuncture is thought to restore the balance. After a long period of intense overload training, athletes` bodies are in this unbalanced state. Therefore the purpose of this research is to investigate the effect of electricacupuncture in controlling cyclists immunocompetency before a competition. Methods A group of 12 cycling athletes from the nation were recruited and divided into two groups; acupuncture group and placebo group. Initial blood samples were collected prior to the athletes` overload training as the primary data. Following the period of overload training, second blood samples were obtained and analysed. The interventions were then introduced, where the acupuncture group received electricacupuncture (zusanli, sanyinjiao on single limbs) once a day for ten days , and the placebo group received a placebo treatment, once a day for ten days. A third and final blood sample was collected before the athletes departed to the city of the competition. Using FACScan (Becton Dicknson) all blood samples were tested for T-lymphocyte cell CD3+%, T-lymphocyte subsets CD4+% CD8+%, the ratio of CD4+ /CD8+ and NK%. We added 20ul of antibody (anti-CD3) by FITC and 20ul antibody [(anit-CD16+56) (IMMUNOTECH)] by PE to 100ul of blood. It was then incubated for 15min and the cell group were determined by FSC and SSC dot-plots. NK cells were analyzed by two-color direct immunofluorescence flow cytometry with FACScan (Beckman Coulter Epics XL). We then added 20ul antibody (anti-CD4) by FITC 20ul antibody (anti-CD8) by PE, and 20ul antibody [(anti-CD3) (IMMUNOTECH)] by PC5 to 100ul of blood. It was then incubated for 15min, and cell groups were determined by FSC and SSC dot-plots. T-lymphocyte subsets were analyzed by threecolor direct immunofluorescence flow cytometry with a FACScan (Beckman Coulter Epics XL). Results After the period of overload training, both groups displayed a significantly marked reduction in the ratio of CD4+ /CD8+ (from 1.85 to 1.49) (P<0.05), NK% was also significantly reduced (from 24.45% to 12.83%)(P<0.05). The third blood sampled revealed that 10 days of electric-acupuncture treatment restored the CD4+ /CD8+ and NK% of the treatment group to near normal levels whilst these measures within the placebo dropped even further (from 1.51 to 1.29)(P<0.05). Conclusions Subsequent to intense overload training, athletes` immune systems are functioning in a strained state, thus heightening the risk of infection before the competition. After being treated with electricacupuncture, immune system function was found to return to a normal level. These findings suggest that electric-acupuncture can be used post intense training as a means of improving immunocompetency in cyclists to provide assurance for performance.